Place attachment and tourist engagement of major visitor attractions in Lisbon - Loureiro, S. M. C.; Sarmento, E. M. (Tourism and Hospitality Research, 2019)
When regarding the literature on engagement, we may find the term associated to co-creation, interactions, processes, levels of knowledge, consumption frequency. Engagement goes beyond involvement and commitment and comprises a proactive relationship between a tourist and the object or place (e.g. attraction). Yet, more research is required to understand the drivers of consumer engagement. Therefore, the aims of the current study are (i) to investigate the relationship between place attachment, place authenticity and tourism engagement, (ii) the mediation role of place authenticity between place attachment and tourism engagement and (iii) the moderation effect of past experience in the relationship between place attachment and tourism engagement. A sample of 346 international tourists to major visitor attractions in Lisbon (capital of Portugal): Belem Tower and Jeronimos Monastery was used. The results indicate a positive correlation between place attachment and tourist engagement, place attachment and place authenticity and between place authenticity and tourist engagement. Place authenticity seems to have a partial mediation between place attachment and tourist engagement. Past experience has also a moderate effect on the relationship between place attachment and tourist engagement. Conclusions, implications and further research are discussed and suggested at the end of the study.